Factors that Cause Unhealthy Eating Behavior in Generation (Gen) Z of Indonesia: a Case Study - Ariestiningsih, Eka Srirahayu; Has, Dwi Faqihatus Syarifah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Students from Gen Z of Health major should already understand the impact of consuming unhealthy food. In reality, they still choose type of food that lack of nutrition. To determine the factors that cause students to consume unhealthy food. The data were collected using in-depth interviews, documentation of alumni research results, and conducting focus group discussion (FGD) with key informants and experts. Data were validated using triangulation credibility testing of sources and methods. The factors causing unhealthy eating behavior of students are the taste, aroma, price of friends' invitations and the main thing is the availability of food. The results of the research show that the factors causing unhealthy eating behavior of students are the taste, aroma, price of friends' invitations and the main thing is the availability of food. Stakeholders should continuously educate students to reduce consumption of unhealthy food by preparing campus canteens and offering healthier food.